Race relations, nationalism and the humanitarian Rohingya crisis in contemporary Myanmar. Issue 2 (4th May 2019) - Mukherjee, Kunal
ABSTRACT: The recent ethnic tensions in Myanmar especially in the Rakhine state has once again placed the country onto the centre stage of global media attention. The aim of this paper is to look at race relations in contemporary Myanmar with a special focus on the Rohingya community. The paper argues that problematic race relations in the country today should be analysed within a certain historical context and should be seen as part of a historical continuum. This paper places a lot of importance on this historical continuum. In this connection, the British colonial policies of divide and conquer, politicians and their obsession with Buddhism and trying to make it the state religion shortly after independence in 1948, and the xenophobic policies followed by the military junta after 1962 deserve special mention. The paper further argues that the current state of affairs and escalation in violence has happened recently because of the convergence of the activities and ideologies of certain political groups like the military junta, the National League for Democracy, the Arakan League for Democracy, and the role played by certain Buddhist extremist groups like the MaBaTha in Burmese politics. To ease the existing tension in the Rakhine, the central government would need to take a more federally minded approach and introduce meaningful democracy and development in the frontier parts of the country where there is a strong ethnic minority presence.